Establishment of a Telecommunications Authority for the Republic of Trinidad and Tobago : White Paper ([The Task Force] [Pot of Spain]TT, 1987)
Looks at the historical dimensions; legal considerations; telecommunications; broadcasting; technical realities; international perspectives; and, makes recommendations for an Authority.
DC